Shift duty and stress coping strategies among nurses in the University College Hospital, Ibadan (2009)
This is an exploratory analytical survey, aimed at identifying the effect of shift duty and the coping strategies-used to adjust to the stress of shift work among rimes working in the University College Hospital, Ibadan in Nigeria. The sample of the study consists of 166 nurses working in various wards selected by a stratified random sampling. The questionnaires were in two sections A and B. Data was collected and analysed using percentages X2, t-test and correlation analysis. Shift duty was reported as stressful by 79 (47.6%) of the nurses studied. Various stress coping responses were identified which were largely based on planning. Neither age nor seniority on the job had any statistical significant influence on the proportion of nurses that report stress from shift work. The positive coping styles correlated negatively with the negative ones but the negative correlations were significant in only two instances namely between planning and denial (P<0.01) and between positive interpretations and growth and alcohol - drug disengagement (P<0.05) Stress coping responses of nurses were largely based on planning and active coping. The finding of this study indicated a need for establishment of counselling unit within the hospital where nurses or even other health workers could be guided and counselled on positive Coping strategies for effective delivery of nursing care to the patients.